Epigenetic Changes in Gene Expression for Drug‐Metabolizing Enzymes and Transporters. Issue 2 (24th October 2013) - Kim, In‐Wha; Han, Nayoung; Burckart, Gilbert J.; Oh, Jung Mi
<x xml:space="preserve">Abstract</x> Individual differences in drug response can be caused by genetic and epigenetic variability and disease determinants. Pharmacoepigenetics is a new field that studies the expression changes in pharmacogenes without changes in DNA sequences. Epigenetic control mechanisms are associated with DNA methylation, histone modification, small noncoding RNAs, and nucleosome remodeling. Researchers are actively attempting to identify epigenetic mechanisms for controlling the expression of enzymes and transporters affecting the metabolism and disposition of drugs. Current evidence suggests that epigenetic changes play a major role in cytochrome P450 enzyme expression, major transporter function, and in interactions with nuclear receptors. A thorough understanding of pharmacoepigenetics provides insight into new approaches to drug discovery and development, provides an understanding of previously observed actions of older drugs, and provides a pathway by which epigenetics can be harnessed to provide better patient‐specific therapy.